Fidel Castro : a biography - Leonard, Thomas M., 1937- (Westport, Conn. : Greenwood Press, 2004)
Examines the life and career of Cuban ruler Fidel Castro, discussing his childhood, education, family, and rise to political power, and including information about the history of Cuba under his leadership.
Growing up in Cuba -- From Moncada to Havana -- The Russians are coming -- Institutionalization and stagnation of Castro's revolution -- Socialismo o muerte.
Includes bibliographical references (pages 131-141) and index.
Keywords: Castro, Fidel, -- 1926-2016.; Cuba -- History -- 1933-1959.; Cuba -- History -- 1959-1990.; Cuba -- Politics and government -- 20th century; Heads of state -- Cuba -- Biography; Cuba -- History -- 1933-1959.; Cuba -- History -- 1959-; Castro, Fidel, -- 1926-2016; Politics and government; Heads of state; Cuba; Castro, Fidel; 1900-1999; Biographies; History; Biographies